Search for Compact Object Coalescences and Understanding Their Significance Using Data from Advanced Ligo - (:unkn) unknown (My University, 2018)
Gravitational waves were observed for the first time on September 14, 2015. A 36 and a 29 solar mass black holes were seen to inspiral around each other and merge about 410 Mpc away. This gave momentum to the areas of gravitational wave astrophysics and astronomy. While the universe could be perceived in the electromagnetic spectrum so far, enabling us to "see" it with telescopes, it could now be "listened to" using gravitational waves. Also, black holes being optically dark, could be observed directly for the very first time after this discovery. The 100 year old theory of General Relativity saw direct evidence through this discovery for the first time. Ever since the first observation, 5 black hole binaries and a binary neutron star have been seen to merge, through gravitational waves. In case of the binary neutron star merger, its electromagnetic counter part, a gamma ray burst was also observed by astronomers, thereby corroborating it. Hence, I have been writing my dissertation in an era of pioneering discoveries. I will try to summarize my contributions to the field at this stage. The major aspects of my work that my dissertation explores, are as follows: 1) contributions to the search for Intermediate mass binary black holes (total masses 100-100000 solar mass) for the first observing run of LIGO that extended between September 12, 2015 and January 14th 2016; 2) preparations for the second observing run of LIGO including helping integrate the search for stellar mass and the intermediate mass binary black holes, so as to have an optimally sensitive combined search; 3) analysis and interpretation of science data during the second observing run which lasted between 30th November 2016 and 26th August 2017. This included work on improving and optimizing the search sensitivity; 4) continued effort on the calculation of astrophysical rates of different populations of compact objects and with the preparation for the next observing run.
Keywords: Advanced LIGO; FGMC; gravitational waves; intermediate mass black hole binary; supernova mass gap; template bank